Performance Comparison of Advanced Transcritical Power Cycles with High-Temperature Working Fluids for the Engine Waste Heat Recovery - Lin, Xinxing; Chen, Chonghui; Yu, Aofang; Yin, Likun; Su, Wen (Energies (Basel), 2021)
To efficiently recover the waste heat of mobile engine, two advanced transcritical power cycles, namely split cycle and dual pressure cycle, are employed, based on the recuperative cycle. Performances of the two cycles are analyzed and compared through the development of thermodynamic models. Under given gas conditions, seven high-temperature working fluids, namely propane, butane, isobutane, pentane, isopentane, neopentane, and cyclopentane, are selected for the two cycles. At the design system parameters, the highest work 48.71 kW, is obtained by the split cycle with butane. For most of fluids, the split cycle has a higher work than the dual pressure cycle. Furthermore, with the increase of turbine inlet pressure, net work of the split cycle goes up firstly and then decreases, while the work of dual pressure cycle increases slowly. For the split cycle, there exists a split ratio to get the maximum network. However, for the dual pressure cycle, the larger the evaporation temperature, the higher the net work. On this basis, system parameters are optimized by genetic algorithm to maximize net work. The results indicate that the highest work 49.96 kW of split cycle is obtained by pentane. For the considered fluids, except cyclopentane, split cycle always has a higher work than dual pressure cycle. Due to the higher net work and fewer system components, split cycle is recommended for the engine waste heat recovery.